Does age influence biltong hunters behaviour? - van der Merwe, Peet, author; Saayman, Melville, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
When looking at market segmentation, age is often used to segment tourism markets. This was also the case with this study, where age was used to perform a market segmentation of South African biltong hunters. The aim was to determine how age affects hunters' behaviour. Data were obtained during the 2015 national hunters' survey. During this time, 492 completed questionnaires were obtained. The results showed that age does affect hunters' behaviour. Firstly, the results revealed that the main motive for hunters to hunt is to escape, to be in nature and to obtain meat; and secondly, age affects hunters' spending and motives to hunt. This research will help product owners to develop different products for hunters based on their age.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.